Treatment of Radioactive Liquid Waste Using Bentonite - Aamir Abdullah Mohammed; Hayder S. Hussain; Salam K. Al-Nasri (Iraqi Journal of Science, 2021)
Radioactive liquid waste contaminated with cesium-137 found in the radiochemistry laboratories at Tuwaitha site, south of Baghdad, was treated in this work. Bentonite was used as a sorbent material for the removal of radioactive cesium-137 from liquid waste by ion exchange method. The results indicated that the best removal efficiency obtained was 95.13% with experimental conditions of 2 h mixture time, 0.04 g sorbent mass, and pH=10 for the radioactive liquid. It was found that the experimental results match well with Langmuir and Freundlich models, with better matching with the latter.